Internalisasi Nilai-Nilai Budaya Religius Melalui Kegiatan Rutin Istighotsah Malam Jum'at Manis - Nurul Azizah; Aannia Kurniawati; Fahrur Razi (Institut Kariman Wirayudha Sumenep, 2023)
This research aims to; 1) how to internalization religious cultural valus trough routine activities “istigotsah malam Jum’at manis” in islamic education Mambaul ulum, 2) what is the purpose of the routine activity, 3) what are the supporting and inhibiting factors?, 4) how effective is the routine activity for students?. This study uses a qualitative research method with a case studi research type. Sources of data obtained through interviews and documentation. Then the researchers carried out data analysis techniques in the Miles and Huberman models. That is, whit data analysis techniques, data reduction, data education, and conclusions drawn. The results of study are, internalization of religius cultural values trough routine activities “istighotsah malam Jum’at manis” in islamic education Mambaul ulum it’s done with four strategies; giving announcements, giving addiction, teaching fairness or custom, and giving punishment. The purpose of this routine activities is; to come closer to god, establish a high social soul, train discipline, maintain and preserve tradition. Supportive factor in this activity is that consciousness emerges, there’s early religious education, and there’s a positive impact of friendship. While the inhibiting factors are, lack of consciousness, the influence of thee use of gadgets over,the lack of early religious knowledge, and the negative influence of friendship. The effectictivinessof these routine activities has gone well. It’s based on research findings in the field, students admit that many have a positive impact, among them, motivation to get closer to God, increase discipline in anything, feel more social soul, and want to preserve tradition “istighotsah malam Jum’at manis” in order not to become extinct.